Retinal pigment epithelial tears after intravitreal bevacizumab injection for neovascular age-related macular degeneration - Chan, Clement K; Meyer, Carsten H; Gross, Jeffrey G; Abraham, Prema; Nuthi, Asha S D; Kokame, Gregg T; Lin, Steven G; Rauser, Michael E; Kaiser, Peter K (Retina (Philadelphia, Pa.), 2007)
To study retinal pigment epithelium (RPE) tears after off-label intravitreal bevacizumab (Avastin; Genentech, Inc., South San Francisco, CA) injection for neovascular age-related macular degeneration. Eyes with a vascularized pigment epithelial detachment (PED) that developed an RPE tear were compared with eyes with a vascularized PED but without an RPE tear. Nine retina specialists across the United States and in Europe participated in this retrospective case series. All eyes that received intravitreal bevacizumab injection for choroidal neovascularization (CNV) over 12 months (October 2005 to September 2006) were included. Eyes without all three confirmed tests (fluorescein angiography, fundus photography, and optical coherence tomography) were excluded from analysis. Statistical analyses were performed on multiple characteristics of eyes with a vascularized PED that did and did not develop an RPE tear. Among 2,785 intravitreal bevacizumab injections for 1,064 eyes, RPE tears were found in 22 eyes in 22 patients (2.2%). A vascularized PED was present in 21 of 22 eyes that developed an RPE tear (17.1% of PED eyes; 15, 100% occult CNV; 6, predominantly occult CNV). Mean interval from bevacizumab injections to RPE tears was 37.3 days. Mean follow-up time was 124.9 days. Mean subfoveal PED size was larger for eyes with tears than for those without tears (13.97 mm vs 9.9 mm, respectively; P = 0.01; odds ratio, 1.09). There was substantially smaller mean ratio of CNV size to PED size for eyes with tears than for those without tears (27.9% vs 67.6%, respectively; P = 0.005). Mean pre-bevacizumab injection best-corrected Snellen visual acuity was 20/162, and mean post-RPE tear best-corrected visual acuity was 20/160 (P = 0.48). Large PED size is a predictor for RPE tears, and a small ratio of CNV size to PED size (<50%) is more common in eyes with RPE tears. Vision may be preserved despite RPE tears.